2012
DOI: 10.1016/j.neuroscience.2012.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Early and late activity in somatosensory cortex reflects changes in bodily self-consciousness: An evoked potential study

Abstract: Abstract-How can we investigate the brain mechanisms underlying self-consciousness? Recent behavioural studies on multisensory bodily perception have shown that multisensory conflicts can alter bodily self-consciousness such as in the ''full body illusion'' (FBI) in which changes in self-identification with a virtual body and tactile perception are induced. Here we investigated whether experimental changes in self-identification during the FBI are accompanied by activity changes in somatosensory cortex by reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 103 publications
(134 reference statements)
8
36
1
Order By: Relevance
“…The current study accords well with the findings of adult studies using the same FBI paradigm (e.g., Aspell et al., ; Aspell et al., ; Lenggenhager et al., ; Lenggenhager et al., ). In our set‐up, participants viewed the body from a third‐person perspective – that is, as if seen by someone else, and not from a first‐person perspective, in the visual reference frame of one's own body.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study accords well with the findings of adult studies using the same FBI paradigm (e.g., Aspell et al., ; Aspell et al., ; Lenggenhager et al., ; Lenggenhager et al., ). In our set‐up, participants viewed the body from a third‐person perspective – that is, as if seen by someone else, and not from a first‐person perspective, in the visual reference frame of one's own body.…”
Section: Discussionsupporting
confidence: 92%
“…The phenomenon of mislocalizing (or mis‐referring) touch to a virtual body is present in adults (e.g., Lenggenhager et al., ; Lenggenhager et al., ; PomĂ©s & Slater, ). It can be measured through questionnaires, and is further evident in implicit measures, that is, changes in cross‐modal congruency effects (Aspell et al., ) and somatosensory evoked potentials (Aspell et al., ) during the illusion. The present study assessed the development of touch referral, and we found that the magnitude of difference between baseline‐corrected questionnaire responses in the synchronous condition and the asynchronous condition increased strikingly with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FBI data show that agreement with illusion statements was signfiicantly higher in synchronous than asynchronous body conditions in the non-ASD group -as found previously (Aspell et al, 2012;Cowie, McKenna, Bremner, & Aspell, 2017;Ionta et al, 2011;Lenggenhager et al, 2007) -but did not differ in the ASD group. Moreover, neurotypical participants showed significantly greater self-identification with the virtual body in the synchronous condition and a greater self-location drift towards the virtual body during the synchronous condition, but this was not found for ASD participants.…”
Section: Discussionsupporting
confidence: 82%
“…This is in line with earlier findings showing that prerequisite embodiment and the observation of highly self-related stimuli (touch on own face; Adler et al, 2016; anatomically matched touch on hands in first-person perspective; Rigato et al, 2019) are associated with vicarious touch effects over P45 specifically. P45 originates in S1 (Allison et al, 1989(Allison et al, , 1992Schubert et al, 2008), which is itself critically involved in vicarious touch for hands in first-person versus third-person perspectives (Schaefer et al, 2012) and in the sense of body ownership (Aspell, Palluel, & Blanke, 2012;Otsuru et al, 2014).…”
Section: Discussionmentioning
confidence: 99%